Influence of internal migration on antenatal care utilization in Bangladesh: Findings from a nationally representative cross-sectional survey - Md. Minhajul; Md. Mahfuzur Rahman; Md Ismail Tareque (PLoS ONE, 2026)
Internal migration plays a crucial role in shaping healthcare utilization patterns, particularly in developing countries. However, its influence on maternal healthcare utilization, especially on antenatal care (ANC) utilization, remains underexplored. This study examines the association between internal migration and receiving antenatal care services among women aged 15–49 years using nationally representative cross-sectional data from the 2022 Bangladesh Demographic and Health Survey. This study analyzed 4,306 currently married women who had at least one live birth in the three years preceding the survey. Descriptive statistics, chi-square tests, and multivariable logistic regression models were employed to examine the association of migration status with receiving professional ANC and quality ANC visits. Our analysis shows that rural-to-urban migrants had the highest likelihood of receiving both professional ANC and quality ANC visits (68.5% and 38.2%, respectively). The adjusted odds ratios show that rural-to-urban migrants were significantly more likely to receive a professional ANC visit (AOR = 1.58, 95% CI: 1.11–2.24) than the urban residents, whereas urban-to-rural migrants were significantly less likely to receive that service (AOR = 0.74, 95% CI: 0.60–0.91) than their urban counterparts. A similar pattern was observed for the utilization of quality ANC (AOR = 0.73, 95% CI: 0.58–0.94) among urban-to-rural migrants. These findings indicate apparent inequalities among different groups of migrant women in their access to maternal healthcare services. Strengthening rural healthcare infrastructure and enhancing awareness about the importance of ANC could help ensure equitable access to maternal health care services in Bangladesh and other countries with similar contexts.